Enhanced cognitive control following neurofeedback therapy in chronic treatment-resistant PTSD among refugees: a feasibility study - Askovic, Mirjana; Murdoch, Sejla; Mayer-Pelinski, René; Watters, Anna J.; Elhindi, James; Aroche, Jorge; Kropotov, Juri D.; Harris, Anthony W.F. (Frontiers in Psychiatry, 2025)
BackgroundPost-traumatic stress disorder (PTSD) is a debilitating condition affecting 3.9% of the global population, with refugee populations experiencing particularly high prevalence rates (23–42%). Cognitive control deficits are a core feature of PTSD and a significant factor in treatment resistance, which affects 25–60% of cases.MethodsThis study examined the effects of neurofeedback therapy (NFT) on PTSD symptoms and cognitive control in forty-seven refugees with chronic treatment-resistant PTSD. Pre- and post-treatment assessments included the Harvard Trauma Questionnaire (HTQ), event-related potential (ERP) and behavioural parameters recorded during a cued Go/No-Go task. Over a median of twenty-six sessions across 7 months, clients received individualised NFT integrated with trauma counselling. Post-treatment, clients were categorised into Responders and Non-Responders, with responders defined as those achieving a clinically significant reduction in PTSD symptoms (≥0.5-point decrease on the HTQ).ResultsResponders (n=22) demonstrated normalised P3d amplitude, indicative of improved cognitive control. In contrast, non-responders (n=25) exhibited minimal changes in ERP measures. Non-responders showed greater abnormalities in the Slow Positive Wave (SPW) at baseline suggesting more compromised late-stage cognitive processing.DiscussionThese findings suggest that NFT can alleviate PTSD symptoms in refugees with chronic treatment-resistant PTSD. Treatment response was associated with a normalisation of the P3d waveform suggestive of enhanced cognitive control. The baseline SPW predicted treatment response. Further research should incorporate randomised controlled trials and larger, multi-centre samples to enhance robustness and generalisability.